2019
DOI: 10.1002/jbmr.3711
|View full text |Cite
|
Sign up to set email alerts
|

Altered Tissue Composition, Microarchitecture, and Mechanical Performance in Cancellous Bone From Men With Type 2 Diabetes Mellitus

Abstract: People with type 2 diabetes mellitus (T2DM) have normal‐to‐high BMDs, but, counterintuitively, have greater fracture risks than people without T2DM, even after accounting for potential confounders like BMI and falls. Therefore, T2DM may alter aspects of bone quality, including material properties or microarchitecture, that increase fragility independently of bone mass. Our objective was to elucidate the factors that influence fragility in T2DM by comparing the material properties, microarchitecture, and mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
107
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 97 publications
(130 citation statements)
references
References 92 publications
9
107
4
1
Order By: Relevance
“…Nonetheless, it is interesting that the mineral distribution is becoming more heterogeneous within this localized region; further studies are required to delineate whether changes also arise in the peripheral regions. Second, by our methods we did not observe altered mechanical properties at the tissue level despite previous observations of increased fracture risk in DB patients at the population level, which is in keeping with the findings of a study that compared the mechanical properties (compression and Reference Point Indentation) of DB femoral cancellous bone to non‐DB OA patients, although another study reported that DB bone had increased stiffness, yield, and ultimate strength . These studies highlight the challenge of delineating the underlying mechanisms for increased fracture risk in DB patients, which might be associated with properties not distinguishable through our approach, in particular, fracture toughness.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Nonetheless, it is interesting that the mineral distribution is becoming more heterogeneous within this localized region; further studies are required to delineate whether changes also arise in the peripheral regions. Second, by our methods we did not observe altered mechanical properties at the tissue level despite previous observations of increased fracture risk in DB patients at the population level, which is in keeping with the findings of a study that compared the mechanical properties (compression and Reference Point Indentation) of DB femoral cancellous bone to non‐DB OA patients, although another study reported that DB bone had increased stiffness, yield, and ultimate strength . These studies highlight the challenge of delineating the underlying mechanisms for increased fracture risk in DB patients, which might be associated with properties not distinguishable through our approach, in particular, fracture toughness.…”
Section: Discussionsupporting
confidence: 86%
“…These studies highlight the challenge of delineating the underlying mechanisms for increased fracture risk in DB patients, which might be associated with properties not distinguishable through our approach, in particular, fracture toughness. Moreover, similar to other studies, we used OA bone as a surrogate control as no healthy human bone was available and, although we could distinguish between the two groups in terms of mineralization, this might explain the lack of difference in mechanical properties. Nano‐indentation and fracture toughness testing is thus required to further investigate whether the increased mineral heterogeneity plays a role in the propensity for DB human bone to fracture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In summary, the study by Hunt and colleagues bridges the gap between epidemiologic and experimental analyses of bone fragility in T2DM. With a careful experimental and theoretical analysis of human T2DM bone quality, the investigators elucidate crucial relationships between bone matrix material properties and bone fragility in this clinically relevant human patient population.…”
Section: Commentarymentioning
confidence: 99%